UNDERSTANDING COGNITIVE INDEPENDENCE AMONG CULTURALLY DIVERSE LEARNERS: EVIDENCE FROM AN INNOVATIVE ASSESSMENT FRAMEWORK - S. KUMARAN ARUL DEVARAM; Dr.S.GUNASEKARAN (The Bioscan, 2026)
Cognitive independence is increasingly recognized as a crucial educational outcome that enables learners to think critically, make informed decisions, solve problems autonomously, and adapt to complex learning environments. In culturally diverse educational settings, understanding variations in cognitive independence becomes essential for promoting inclusive and equitable learning opportunities. This study investigates cognitive independence among learners from diverse cultural, linguistic, and socioeconomic backgrounds through the implementation of an innovative assessment framework specifically designed to evaluate autonomous thinking, self-regulated learning, decision-making ability, reflective judgment, and problem-solving competence. The framework integrates quantitative assessment measures with qualitative observations to provide a comprehensive understanding of learner autonomy across different educational contexts. The study was conducted among undergraduate students representing varied demographic groups. Data were collected using a Cognitive Independence Assessment Device and analyzed through descriptive and inferential statistical techniques. The findings reveal significant improvements in learners’ ability to engage in independent reasoning, critical evaluation, and self- directed learning activities. The results further indicate that culturally responsive assessment practices help reduce biases often associated with conventional evaluation methods and provide a more accurate representation of learners’ cognitive capabilities. The study highlights the importance of innovative assessment frameworks in fostering educational equity, supporting diverse learners, and promoting lifelong learning skills. The findings offer valuable implications for educators, curriculum developers, and policymakers seeking to strengthen inclusive educational practices and learner autonomy in multicultural learning environments.